The school, a space for meeting and emotion, or a place of animosity? - Hernández Méndez, Griselda (IE Revista de Investigación Educativa de la REDIECH, 2021)
This text intends for the reader to reflect on the degree of importance that has been given to educational reforms, especially for the basic level, which, in response to the new social, economic and political requirements, imply forced changes, different ways of teaching. Throughout the pages it is questioned what those changes are and what the role of teachers has been in dealing with them. It is detected that both teachers and parents, determined by what society demands and, therefore, educational reform, prepare children to be able to respond to these demands, avoiding the children’s own nature, imperceptibly leading them to detest the school while in the discourse the reform praises paidocentrism, meaningful learning, emotions and more. This would suppose a different school to the one attended with delight and initiative on the part of the students, hence the title implies a question mark. It is not about formulating an expeditious response, nor is it looking for its determinants, precisely because it is about unveiling the complexity of the school and its practices, in a constructive evolution, in a continuous resizing and contextualization.